2022
DOI: 10.20944/preprints202004.0316.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early Crop-Type Mapping Under Climate Anomalies

Abstract: Crop-type mapping is an important intermediate step for cost-effective crop management at the field level, as an overview of all fields with a particular crop type can be used for monitoring or yield forecasting, for instance. Our study used a data set with 2400 fields and corresponding satellite observations from the federal state of Bavaria, Germany. The study classified corn, winter wheat, winter barley, sugar beet, potato, and winter rapeseed as the main crops grown in Upper Bavaria. We additionally experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…However, the ability to generalize over multiple years has not been thoroughly studied [20]. Marszalek et al [22] used Random Forest (RF) and Support Vector Machines (SVM), which have shown promise but are not scalable and require re-training for each additional observation with multi-year data.…”
Section: Crop Classificationmentioning
confidence: 99%
“…However, the ability to generalize over multiple years has not been thoroughly studied [20]. Marszalek et al [22] used Random Forest (RF) and Support Vector Machines (SVM), which have shown promise but are not scalable and require re-training for each additional observation with multi-year data.…”
Section: Crop Classificationmentioning
confidence: 99%
“…The crop mapping task was evaluated on a data set which included the main crop types (corn, winter wheat, winter barley, winter rapeseed, sugar beet, and potato) in Upper Bavaria (Germany), collected for the years 2016, 2017 and 2018 (Figure 1). It is part of a larger collection, assembled and partly self-created, which included crop types and yields for different regions (Marszalek, 2021). The climatological data in Table 1 provided better insights into the various climatological conditions.…”
Section: Study Sitementioning
confidence: 99%
“…Initially, all 13 bands were used in this study. A more detailed band description with properties can be found in (GEE, 2012) or (Marszalek et al, 2020). For this purpose, Level-1C data were downloaded from Google Earth Engine (GEE) (Google, 2020), but not further processed to bottom-of-atmosphere (BOA) reflection information since the focus was the comparison of supervised learning with self-supervised learning.…”
Section: Sentinel-2mentioning
confidence: 99%
See 1 more Smart Citation
“…By addressing the motivating use-case of crop type classification using this reference dataset, data-driven methods will implicitly learn internal representations of vegetation dynamics, i.e., its phenology. Such models can further be used to monitor the development of vegetation stocks to spot unexpected patterns, e.g., caused by environmental influences [6], or to predict the expected yield [5]. Furthermore, the country-specific statistics compiled and harmonised in EUROCROPS allow for statistical investigation of regional distributions of crop cultivation patterns (cf.…”
Section: Fields Of Applicationmentioning
confidence: 99%